2022
DOI: 10.3390/ijms232113249
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Resistive Switching and Synaptic Characteristics of ALD Deposited AlN-Based RRAM by Positive Soft Breakdown Process

Abstract: Nitride film played an essential role as an excellent diffusion barrier in the semiconductor field for several decades. In addition, interest in next-generation memories induced researchers’ attention to nitride film as a new storage medium. A Pt/AlN/TaN device was investigated for resistive random-access memory (RRAM) application in this work. Resistive switching properties were examined in the AlN thin film formed by atomic layer deposition (ALD). The unique switching feature conducted under the positive vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Widely used and reliable RRAM devices to date are based on insulating TMOs such as Al 2 O 3 [14], TaO x [15], and TiO 2 [16]. The fabrication of TMOs-based RRAM devices relies on techniques such as chemical vapor deposition [17,18], and atomic layer deposition [19,20], which limits their application for flexible memristor devices. Hence, ultrathin twodimensional nanomaterials i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Widely used and reliable RRAM devices to date are based on insulating TMOs such as Al 2 O 3 [14], TaO x [15], and TiO 2 [16]. The fabrication of TMOs-based RRAM devices relies on techniques such as chemical vapor deposition [17,18], and atomic layer deposition [19,20], which limits their application for flexible memristor devices. Hence, ultrathin twodimensional nanomaterials i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, an unstable interface is formed between the electrode and the insulating layer, creating fluctuations in cycle-to-cycle uniformity because of the high reactivity of oxygen ions [28,29]. Recently, studies have focused on nitride-based insulating layers such as AlN [30], SiN [31,32], and WN [33] because of their excellent electrical properties and ionic chemistry, providing a choice to solve the mentioned problems of metal oxides [34,35]. The performance of SiN-based resistive switching devices compared with metal-oxide-based resistive switching devices is summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Among the above metal oxides, TaO x is known as the leading oxide material that shows outstanding memory characteristics such as high endurance (>10 10 ), fast switching speed (<1 ns), and good scalability (<30 nm) [ 21 , 22 , 23 , 24 , 25 ]. Moreover, some researchers reported that the TaO x layer can create oxygen vacancies easily, indicating that it has benefits in forming strong conductive filaments, further supporting its non-volatile memory device application [ 26 , 27 , 28 ]. However, several issues such as uniformity in operating voltage and resistance state still exist.…”
Section: Introductionmentioning
confidence: 99%